Wireless vision-based fuzzy controllers for moving object tracking using a quadcopter - Mohammed Algabri; Hassan Mathkour; Mohamed Amine Mekhtiche; Mohamed Abdelkader Bencherif; Mansour Alsulaiman; Mohammed Amer Arafah; Hamid Ghaleb (International Journal of Distributed Sensor Networks)
During the last few decades, the utilization of unmanned aerial vehicles has grown in military and has seen new civil applications because of their reduced cost and hovering capabilities. This article presents a visual servoing system for detecting and tracking a moving object using an unmanned aerial vehicle. The system consists of two sequential components. The first component addresses the detection of a moving object, using the unmanned aerial vehicle based on color features. The second component addresses the visual servoing control that is designed to guide the unmanned aerial vehicle according to the target position and inclination. Three fuzzy logic modules are implemented in order to control the unmanned aerial vehicle in tracking a moving object. The proposed method is validated on a real flight using an AR.Drone 2.0 quadcopter. The obtained results show that the performance of the proposed method is suitable for object-following tasks in surveillance applications. This research investigates the use of unmanned aerial vehicle technology for crowd monitoring during Hajj and it could also be used for border surveillance to monitor Saudi Arabia’s borders.